ANÁLISIS SOCIOECONÓMICO DE LA PRODUCCIÓN DE POLLOS BROILERS EN EL CANTÓN EL EMPALME: CASO EMPRESA “AGRÍCOLA Y PECUARIOS GUERRERO” AÑO 2022 - Solorzano Espinel, Jairo Jahir (2023)
In order to analyze the socioeconomic situation in the production of broiler chickens in El Empalme canton, Guayas province, a descriptive investigation was carried out under a non-experimental approach. ¨A single case study was selected, being "Agrícola y pecuarios Guerrero" the company selected for the work, with the informed consent of the producer. The study consisted of a diagnosis of the socioeconomic situation of the producer and his family, described his production system, and obtained some financial indicators of the activity (Costs, income, profitability, break-even point, IRR and VAN).